Historical Factors Associated With Past Environments Influence the Biogeography of Thermophilic Endospores in Arctic Marine Sediments - Hanson, China A.; Müller, Albert L.; Loy, Alexander; Dona, Clelia; Appel, Ramona; Jørgensen, Bo Barker; Hubert, Casey R. J. (Frontiers in Microbiology, 2019)
Selection by the local, contemporary environment plays a prominent role in shaping the biogeography of microbes. However, the importance of historical factors in microbial biogeography is more debatable. Historical factors include past ecological and evolutionary circumstances that may have influenced present-day microbial diversity, such as dispersal and past environmental conditions. Diverse thermophilic sulfate-reducing Desulfotomaculum are present as dormant endospores in marine sediments worldwide where temperatures are too low to support their growth. Therefore, they are dispersed to here from elsewhere, presumably a hot, anoxic habitat. While dispersal through ocean currents must influence their distribution in cold marine sediments, it is not clear whether even earlier historical factors, related to the source habitat where these organisms were once active, also have an effect. We investigated whether these historical factors may have influenced the diversity and distribution of thermophilic endospores by comparing their diversity in 10 Arctic fjord surface sediments. Although community composition varied spatially, clear biogeographic patterns were only evident at a high level of taxonomic resolution (>97% sequence similarity of the 16S rRNA gene) achieved with oligotyping. In particular, the diversity and distribution of oligotypes differed for the two most prominent OTUs (defined using a standard 97% similarity cutoff). One OTU was dominated by a single ubiquitous oligotype, while the other OTU consisted of ten more spatially localized oligotypes that decreased in compositional similarity with geographic distance. These patterns are consistent with differences in historical factors that occurred when and where the taxa were once active, prior to sporulation. Further, the influence of history on biogeographic patterns was only revealed by analyzing microdiversity within OTUs, suggesting that populations within standard OTU-level groupings do not necessarily share a common ecological and evolutionary history.